PENGARUH IMPREGNASI LOGAM TITANIUM PADA ZEOLIT ALAM MALANG TERHADAP LUAS PERMUKAAN ZEOLIT - Rianto, Lalang Budi; Amalia, Suci; Khalifah, Susi Nurul (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2012)
Effort that can maximize the working of natural zeolite is by activation and modification as a carrier of active metals or commonly called impregnation. Modified zeolite by impregnation using titanium metal is to increase the performance of a pure metal catalysts such as low in thermal stability, decreasing surface area and sintering occurs (clotting) and expensive in the application. Bearers Treatment in the metallic solids by impregnating the zeolite would make the metals in zeolites as bifungsional catalysts.Modified Malang’s natural zeolite starting with the activation process using a solution of NH4NO3 2 M, continued by the addition of titanium metal used in zeolite TiO2 solution with a concentration of 0.1, 0.2, and 0.3 M. Modified zeolite crystallinity characterized analized by XRD analysis. Methylen blue adsorption on Ti-zeolite is to measure the specific surface area. SEM surface morphology analysis is used to determine the content of the element is by using XRF analysis.Characterization using XRD analysis results indicate that Malang’s natural zeolite not changed in the structure, but it changes the intensity due to the addition of titanium. The largest surface area measurement obtained from the treatment of Ti-zeolite 0.1, 0.2 and 0.3 M are : 23.159; 23.077 and 20.848 m2/gr. SEM analysis showed that titanium metal dispersion fairly evenly after the modification. While from the XRF analysis showed that the ratio of Si / Al increased to 4.354 and content of titanium in the Ti-natural zeolite Malang is 13.6%.